The Impact of Introductory Anatomy Laboratory Videos on Medical Students’ Laboratory Quiz Performance - Stefanus Satria Sumali; Mona Marlina (Medicinus, 2026)
Background: This study examined the association between viewing introductory anatomy laboratory videos and quiz performance among medical students at the Faculty of Medicine, Universitas Pelita Harapan.   Methods: Using observational design with a cross-sectional approach of secondary data from 180 students in the Skin and Special Senses course.   Result: Students who watched the introductory video were significantly more likely to achieve quiz scores of ≥60 than those who did not. Chi-square analysis demonstrated a significant association between video viewing status and quiz performance (χ²(1)=40.36, p<0.001), with a moderate relationship strength (Cramér’s V=0.474). Students who watched the video were nearly eight times more likely to achieve passing scores (OR=7.91, 95% CI: 4.06–15.42).   Conclusions: Watching introductory anatomy laboratory videos was significantly associated with better laboratory quiz performance. It may support self-directed learning and enhance the academic performance.